ANALYSIS OF PROVIDER-INITIATED HIV TESTING AND COUNSELING IN TUBERCULOSIS PATIENT AT A PRIVATE HOSPITAL IN JAKARTA - Vandauli, Melanie; Bachtiar, Adang (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Stigma, lack of knowledge about HIV risks to oneself, openness, limited access to health services and aspects of gender inequality are determinants that influence the willingness to take HIV tests in the context of VCT. However, studies in the context of PITC have not been widely publicized in Indonesia, particularly studies in private hospitals. Analysis related to the reason that influence the willingness of health workers to carry out PITC in TB patients is important to do. The purpose of this study is to analyze the reason that influence the willingness of health workers to carry out PITC in TB patients. Methods: This study is a quantitative study with cross-sectional design. The study was conducted at a private hospital in Jakarta. The sampling technique used total sampling techniques, where the entire population was sampled. the research sample obtained is 30 doctors who have TB patients in the private hospital during March to April 2019. Results: The majority of doctors (46.7%) were sometimes willing to do the PITC in TB patients. The proportion of doctors who are always willing to do the PITC in TB patients is still low at 20%. On the other hand, there were 33.3% doctors were never willing to do the PITC on TB patients. The reason that influences the doctor's willingness to do PITC on TB patients is the possibility to explain (66.7%), automatically as requested in the rules (20,0%) and the severity of the TB case (13,3%). Conclusions: The biggest reason that influences the doctor's willingness to do PITC on TB patients is the possibility to explain. Doctors are often difficult to explain the importance of HIV testing for TB patients due to the thick negative stigma associated with HIV testing. the government should encourage socialization regarding the importance of HIV testing for both TB patients and high-risk HIV groups. The key challenge to improving health care delivery is to improve the implementation and monitoring of effective interventions.